Winter wolves [large type] - Mayo, Matthew P. (A Roamer western, 2023)
"One mans quest to lose himself in the West. Roamers long-planned winter snowshoe trek to the high, lonesome peaks of the Bitterroots takes a hard turn when the big loner of a woodsman finds his mentor, cantankerous mountain man Maple Jack, savaged, terrorized, and raving about the Alooknok, blood-eyed demons who absconded with his cold-weather mate, Winter Woman, a no-nonsense healer and midwife. Its up to Roamer to rescue her. He takes to the trail in the wake of a blizzard, battling winter-starved timber wolves and the unforgiving elements. Tracking him, the addled Maple Jack falls prey to a trio of greasy wolfers. Then the very demons Roamer seeks find him-and force him deep into the belly of the beast, a foreboding, grim place in the raw mountains where sunlight never shines. A brutal battle among friends, enemies, and Alooknok will seal their fates and haunt the few survivors ... forever"--